Pengaruh Ukuran Perusahaan, Profitabilitas, Leverage, Dan Kinerja Lingkungan Terhadap Environmental Disclosure - Agus Maulana; Eva Theresna Ruchjana; Dian Hakip Nurdiansyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
The background of this study is intend to identify, analyse, and describe the effect of size company, profitability, leverage, and environmental performance on environmental disclosure. The data on this uses a descriptive verificate research with a quantitative approach. In this study, used researches purposive sampling to determine the samples. This research using the secondary data taken from annual report that is published by companies sample. While in the process of data analysis in this research using SPSS 26 software consisting of classical assumption test (normalitas test, autocorrelation test, heteroskedastisity test and multicolinearity test) double regresilinear analysis, hypotesis test (t statictical test and F statistical test) and coefficient of determination test. The result of reseach is profitability has a negative influence on environmental disclosure. As for the size company, leverage, and environmental performance have no influence on environmental disclosure. Keywords: Company Size, Profitability, Leverage, Environmental Performance, Environmental Disclosure.